Mythologies of martial arts - Bowman, Paul, 1971- (Martial arts studies., 2017)
What do martial arts signify today? What do they mean for East-West cross cultural exchanges? How does the representation of martial arts in popular culture impact on the wide world? What is authentic practice? What does it all mean? From Kung Fu to Jiujitsu and from Bruce Lee to The Karate Kid, Mythologies of Martial Arts explores the key myths and ideologies in martial arts in contemporary popular culture. The book combines the author's practical, professional and academic experience of martial arts to offer new insights into this complex, contradictory world. Inspired by the work of Roland Barthes in Mythologies, the book focusses on the signs, signifiers, and practices of martial arts globally. Bringing together cultural studies, film studies, media studies, postcolonial studies with the emerging field of martial arts studies the book explores the broader significance of martial arts in global culture. Using an accessible yet theoretically sophisticated style the book is ideal for students, scholars and anyone interested in any type of martial art.